Usia Pemberian Makanan Pendamping Air Susu Ibu (Mp-Asi) Dengan Gangguan Perkembangan Motorik Halus Bayi - Sylvi Wafda Nur Amellia; Suherni; Margono (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: Discovered over 200 million children below five years is not developing according to age. Bantul districtin the year 2008 there is still early detection of growth that have not reached 100%, based on data from at thePHC Imogiri I 78,88%, PHC Imogiri II82,06%. While the number of babies who are given exclusive breast feedingat the PHC Imogiri I 45,75% and PHC Imogiri II19,59%. In the area of PHC Imogiri I, found delays in the developmentof age-appropriate or not is in the village of Wukirsari 6 of 284 infants, in the village of Girirejo 2 of 50 infants,in the village of Karangtalun 3 of 7 infants, and in the village of Imogiri 1 of 42 such infants and there 5 infants whoexperience age-appropriate development was not on fine motor development.Objective: To determine the correlation grant of age complementary feeding with interference trend growth finemotor in the area of work Public Health Center Imogiri I, Bantul, Yogyakarta.Method: The study was an analytical survey with cross sectional approach. The subjects were 0-12 month-old babyat the PHC Imogiri I sample as many as 413 infants with 133 infants using a quota sampling technique. This is achecklist of research instruments and sheet DDST II. Analysis of data using multivariate statistical test that is chisquare with significancy 0,05 level.Results: The proportion of infants who were given complementary feeding before the age of 6 months was 26,3%,infants who experienced fine motor development according to age as much as 73,3%. The magnitude of risk infantsexperiencing fine motor developmental delay infants who were given complementary feeding before the age of 6months was 31,4% and the risk of infants experiencing fine motor developmental delay infants given complementaryfeeding 6 months starting from the age of 6,1%.Conclusion: The administration of the complementary feeding before the age of 6 months are risk factors of theoccurrence of fine motor development disorders in infants.Keywords: Giving Complementary Feeding, Fine Motor Development